Risk analysis and control for industrial processes : gas, oil and chemicals : a system perspective for assessing and avoiding low-probability, high-consequence events /: gas, oil and chemicals : a system perspective for assessing and avoiding low-probability, high-consequence events. ([2015]) - Pasman, H. J
No abstract available